Study on Solid Phase Extraction and Spectrophotometric Determination of Palladium with MCI GEL CHP 20Y as Sorbent - Li, Yang; Yang, Xin-Zhou; Li, Xeu-Sen; Yao, Fu-Quan; Hu, Qiu-Fen (Asian Journal of Chemistry, 2011)
In this paper, a new method for the determination of palladium based on the rapid reaction of palladium with 2-(3,5-dichlor-pyridylazo)-5-dimethylaminoaniline (3,5-diCl-PADMA) and the solid phase extraction of the coloured chelate with a reversed phase MCI GEL CHP20Y resin has been developed. In the presence of 0.05-0.50 mol L-1 of hydrochloric acid solution and cetyltrimethylammonium bromide (CTMAB) medium, 3,5-diCl-PADMA reacts with palladium to form a purple chelate of a molar ratio 1:3 (palladium to 3,5-diCl-PADMA). This chelate was enriched by the solid phase extraction with a MCI GEL CHP 20Y cartridge and eluted the retained chelate from the cartridge with ethanol. The enrichment factor of 100 was achieved. Beer's law is obeyed in the range of 0.01 to 3.0 μg mL-1 in the measured solution. The relative standard deviation for 11 replicates sample of 0.5 μg L-1 level is 3.2 %. The detection limit, based on the three times of standard deviation is 0.05 μg L-1 in the original sample. This method was applied to the determination of palladium with good results.